2020
DOI: 10.32473/jpic.v4.i2.p5
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Pluralism, and Digital Social Advocacy in Nonprofit Strategic Communications

Abstract: This qualitative study investigates the use of acculturation-themed images in nonprofit strategic communications and digital advocacy efforts of 13 organizations serving Hispanic and Latinx immigrant communities in two U.S. states. The study analyzes data from 14 in-depth interviews with the public relations and marketing communication professionals responsible for the website content and digital strategy for the organizations. Based on study findings, the authors argue that these nonprofits are using their we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Finally, the PIC study of nonprofit digital social advocacy directed by Adams and Johnson (2020) found nonprofit engagement on a continuum of "soft" and "hard" efforts, with soft digital advocacy focusing on connections, community-building, and positivity, and hard digital advocacy focusing on direct, explicit calls to action such as protesting or voting against bills (p. 20). Adams and Johnson (2020) argue that "notions of digital social advocacy should be expanded beyond the call for direct action (use of social media for mobilization) to consider the role of soft advocacy done by nonprofits representing marginalized individuals in society" (p. 21). Specifically related to this study, soft advocacy to represent survivors of human trafficking may be just as critical as the Junior League's hard advocacy efforts, especially to address the noted gap of partnerships between members and survivors.…”
Section: Digital Activismmentioning
confidence: 99%
“…Finally, the PIC study of nonprofit digital social advocacy directed by Adams and Johnson (2020) found nonprofit engagement on a continuum of "soft" and "hard" efforts, with soft digital advocacy focusing on connections, community-building, and positivity, and hard digital advocacy focusing on direct, explicit calls to action such as protesting or voting against bills (p. 20). Adams and Johnson (2020) argue that "notions of digital social advocacy should be expanded beyond the call for direct action (use of social media for mobilization) to consider the role of soft advocacy done by nonprofits representing marginalized individuals in society" (p. 21). Specifically related to this study, soft advocacy to represent survivors of human trafficking may be just as critical as the Junior League's hard advocacy efforts, especially to address the noted gap of partnerships between members and survivors.…”
Section: Digital Activismmentioning
confidence: 99%